(untitled) (LACCEI, 2024)
Inequality of opportunity for the hearing impaired has been a problem for many years. Hearing impaired people find it difficult to communicate effectively with hearing people because most people do not know sign language. This research seeks to provide a tool that facilitates and helps people to learn sign language and achieve communication between the hearing impaired and hearing people. For the development of the prototype, it was necessary to approach the hearing-impaired people, an electrical analysis to know the variation of flexibility of people, the design of a PCB personality board and the design of a 3D glove. Then the assembly of the electrical components to the glove was done and a pilot test was conducted with students of the faculty of engineering, where positive results were obtained on the programming at the time of performing the desired letter. Finally, a prototype was created that allowed the translation of the Honduran sign language alphabet through the development of an application that included a voice command to reproduce the formed word.